1985
DOI: 10.1620/tjem.147.247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intragastric ethanol administration on gastric acid secretion and gastrointestinal hormone release in dogs.

Abstract: Dogs with a vagally denervated (Heidenhain) pouch and a gastric fistula were used to investigate the humoral mechanism which would affect the gastric acid secretion following acute intragastric ethanol administration. Ethanol solutions induced a doserelated secretion of gastric acid. Although plasma gastrin levels increased after the loading of both 20% and 30% ethanol solutions, there was a discrepancy between total acid output and the integrated gastrin response. Plasma secretin levels also augmented after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Acute, chronic alcohol consumption affects motility, causing mucosal inflammation and cancer of the oesophagus and stomach (Franke et al ., 2005b). Ethanol stimulates both gastric acid and pancreatic exocrine secretion (Cooke, 1972;Imamura et al ., 1985;Tachibana et al ., 1996), however, it inhibits oesophageal contractility in cats (Keshavarzian et al ., 1994), and the motility of rabbit sphincter of Oddi (Sari et al ., 2004). Ethanol also decreases the amplitude and frequency of phasic contractions of canine antral smooth muscle (Sanders and Bauer, 1982), and cat gastric corpus (Sim et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Acute, chronic alcohol consumption affects motility, causing mucosal inflammation and cancer of the oesophagus and stomach (Franke et al ., 2005b). Ethanol stimulates both gastric acid and pancreatic exocrine secretion (Cooke, 1972;Imamura et al ., 1985;Tachibana et al ., 1996), however, it inhibits oesophageal contractility in cats (Keshavarzian et al ., 1994), and the motility of rabbit sphincter of Oddi (Sari et al ., 2004). Ethanol also decreases the amplitude and frequency of phasic contractions of canine antral smooth muscle (Sanders and Bauer, 1982), and cat gastric corpus (Sim et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of these responses after i.g. ethanol infusion, as indicated by Imamura et al (1985), is probably elevation of gastric acid secretion by the infused ethanol. This elevation in turn, increases the duodenal intraluminal acid load, thereby inducing secretin secretion which causes a secondary stimulation of pancreatic juice secretion.…”
Section: Discussionmentioning
confidence: 95%
“…The results obtained in this study indicated that alcohol is rapidly absorbed after oral intake, with plasma concentrations reaching a peak after about 30 min, with limited individual variation. Biological responses that may affect the pancreas after oral or intragastric administration of alcohol include increased tension in the sphincter of Oddi in the duodenum 9 and increased gastric secretion in the stomach, 10,11 resulting in increased pancreatic exocrine secretion due to the stimulation of secretin caused by the lowering of the duodenal pH. The elevation of secretin and the enhancement of pancreatic secretion that occur approximately 1 h after the administration of alcohol are thought to be due to gastric secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of secretin and the enhancement of pancreatic secretion that occur approximately 1 h after the administration of alcohol are thought to be due to gastric secretion. 10,12 However, there is some variation in the effects of alcohol intake on the stomach: beverages such as beer and wine stimulate gastric secretion, whereas distilled spirits such as whisky and vodka do not. 13 -15 Straus et al 16 suggested that the direct effects of alcohol on the duodenum were also important, but this requires clarification.…”
Section: Discussionmentioning
confidence: 99%